Study of the Biological Characteristics and Oil Content of Date Palm (Phoenix dactylifera L.) Pollen during Different Periods of the Male Spathe Season - Alpresem, Wasen F.F.; Alnajjar, Mohammad A.H (Basrah Journal Of Date Palm Research, 2025)
The study was conducted in the Medicinal and Aromatic Plants Unit, College of Agriculture, University of Basrah, on pollen grains of three male date palm cultivars: Al-Ghanami Al-Akhdar, Al-Deiri, and a seedling type. The objective was to investigate their biological characteristics and oil content during three stages of the male spathe season. These stages included the early stage (at the beginning of emergence), the middle stage (at maturity before sheath splitting), and the late stage (after full spathe opening). The results showed that the male cultivar Al-Deiri significantly outperformed the other cultivars in all studied traits, recording the highest values for pollen viability percentage, pollen germination percentage, pollen tube length, pollen oil percentage, specific gravity, oil density, and refractive index, with respective averages of 82%, 70.67%, 130 µm, 0.039%, 0.837, 0.773 mg µL⁻¹, and 1.440. Regarding the effect of spathe collection periods, the late stage recorded the highest averages for all studied traits compared to the other stages, with respective values of 95.67%, 79%, 120 µm, 0.043%, 0.886, 0.935 mg µL⁻¹, and 1.473. Moreover, the interaction between the Al-Deiri cultivar and the late stage showed a highly significant effect, achieving the best results for all traits, with corresponding averages of 98%, 85%, 160 µm, 0.052%, 0.970, 0.980 mg µL⁻¹, and 1.550.